Determining the Competencies of Educational Administrators in Turkish Education System and These Competency Degrees by Multi-Criteria Decision Making - (:unkn) unknown (TURKISH EDUCATION ASSOC, 2020)
The main aim of this research is to determine the dimensions, the importance level and the weight of the main competencies of sub-competencies that educational administrators should hold. And to propose a systematic model for assignment of educational administrators is another aim. To reach this aim, literature is reviewed, expert opinion is gotten and eight main competencies and sub-competencies of them are identified. One of the Multi-Criteria Decision Making methods - Analytical Hierarchy Process which allows evaluation of subjective and objective qualities together - is used. Depending on Analytical Hierarchy Process method, the competencies are derived by a group of 10 people containing academics and educational administrators who have at least 10 years of field experience. According to the results, main competencies that educational administrators should hold are leadership, administration of educational programs and environment, creating an effective communication and working environment.
Keywords: Competencies of Educational Administrators; Multi-Criteria Decision Making; Analytic Hierarchy Process; Education Administrator; Education Leadership; ANALYTIC HIERARCHY PROCESS; SCHOOL ADMINISTRATORS; INSTRUCTIONAL LEADERSHIP; PROCESS AHP; PRINCIPALS; TEACHERS; CULTURE; BEHAVIORS; SELECTION; OPINIONS